1994
DOI: 10.1103/physrevlett.73.1291
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Transport Properties in SuperconductingNd1.85Ce0.15Cu

Abstract: We report a comprehensive study of the in-plane transport properties of Nd2 "Ce Cu04 & epitaxial thin films and crystals by both increasing and decreasing 6 with Ce content fixed at x = 0.15. We find a remarkable correlation between the appearance of superconductivity and (1) a positive magnetoresistance in the normal state, (2) a positive contribution to the otherwise negative Hall coefficient, and (3) an anomalously large Nernst effect. These results strongly suggest that both holes and electrons participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
147
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 18 publications
14
147
2
Order By: Relevance
“…2,3,4,5,6,7 Similar feature has been observed with changing the oxygen content. 4,8 In another ntype cuprate P r 2−x Ce x CuO 4+δ (PCCO), the change of R H sign with temperature 9,10,11 and doping 12 were also observed. Those strange behaviors strongly indicate that at moderate doping, NCCO and PCCO have two bands with different types of charge carriers, one is hole carrier and the other is electron carrier.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…2,3,4,5,6,7 Similar feature has been observed with changing the oxygen content. 4,8 In another ntype cuprate P r 2−x Ce x CuO 4+δ (PCCO), the change of R H sign with temperature 9,10,11 and doping 12 were also observed. Those strange behaviors strongly indicate that at moderate doping, NCCO and PCCO have two bands with different types of charge carriers, one is hole carrier and the other is electron carrier.…”
supporting
confidence: 77%
“…1 However, R H and thermoelectric power gradually increase and eventually change sign to positive with further doping Ce. 2,3,4,5,6,7 Similar feature has been observed with changing the oxygen content. 4,8 In another ntype cuprate P r 2−x Ce x CuO 4+δ (PCCO), the change of R H sign with temperature 9,10,11 and doping 12 were also observed.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…However, point contact tunneling 10 , penetration depth 11,12 and specific heat 13 revealed some s-wave features in the optimally-doped and overdoped samples, and led to the suggestion of a d-wave to s-wave symmetry transition upon doping or lowering the temperature below 4K. Transport and ARPES measurements have shown that the Fermi surface of the n-doped cuprates evolves from electron-like to hole-like upon doping, with a two-carrier behavior around the optimal doping 14,15 . Recently, it was proposed that Fermi surface topology may influence the pairing symmetry which lead to a symmetry mixing and/or a symmetry transition upon doping 9,16 .…”
mentioning
confidence: 99%